The Impact of Social Media Influencers on Consumer Behaviour: An Analysis Based on Promotion Mix - Haeruddin, M. Ilham Wardhana (Southeast Asia Journal of Business, Accounting, and Entrepreneurship, 2025)
By synthesizing a wide range of existing literature, this study provides a comprehensive overview of the current landscape, revealing how influencers operate within the intricate web of social media. Additionally, the article analyses several case studies that illustrate the effectiveness of influencer marketing campaigns across different industries. These case studies serve to uncover the specific mechanisms through which influencers impact consumer behaviour, such as creating a sense of trust, fostering community engagement, and enhancing brand visibility. The findings underscore the critical importance of authenticity in influencer partnerships; consumers are more likely to respond positively to influencers who are perceived as genuine and relatable. Moreover, the research emphasises the role of engagement in driving consumer action. Influencers who actively interact with their audience tend to create stronger emotional connections, leading to increased brand loyalty and higher conversion rates. The study also discusses the strategic incorporation of influencers into the broader promotional framework, suggesting that marketers should consider factors like audience alignment, content relevance, and the timing of campaigns. In conclusion, the article offers practical recommendations for marketers looking to harness the power of influencer partnerships effectively. By understanding the dynamics of influencer marketing and its impact on consumer behaviour, brands can craft targeted strategies that resonate with their audiences, ultimately enhancing their marketing effectiveness in the competitive digital landscape. This research contributes valuable insights for both academics and practitioners in the field of marketing.